Improving partnerships to improve outcomes for children and young people with special educational needs and disabilities: qualitative findings from a mixed methods systematic review - Tyldesley-Marshall, Natalie; Johnson, Rebecca; Parr, Janette; Brown, Anna; Ghosh, Iman; Mehrabian, Amin; Chen, Yen-Fu; Grove, Amy (Frontiers in Education, 2025)
BackgroundEffective collaboration between different services is recommended by government policy for children and young people (CYP) with Special Educational Needs and Disabilities (SEND) across many countries. In the UK, despite significant shifts in policy towards partnership working, there remains a scarcity of scientific evidence on how this should be achieved. This mixed methods systematic review examined interventions leading to improved service outcomes for multiagency working for CYP with SEND.MethodEleven databases generated a total of 7,473 results. Data from 137 selected studies were analysed. However, only qualitative research findings from thematic synthesis regarding key ingredients of effective partnership are reported.ResultsFrom these, five key ingredients for effective partnership working in SEND services were identified: (1) participation, and legitimacy to participate in a partnership; (2) personalisation and consultation with children, young people, and their families in designing and delivering services; (3) respectful communication, and feeling that involvement is valued; (4) preparation to be an effective member of a partnership; and (5) working across professional and organisational boundaries.Conclusion and implicationsTo facilitate practical application of the findings, three exemplar cases of effective partnership are explored. A framework to support partnership design, collaboration, and the development of evidence-based recommendations, is presented.Systematic review registrationThe study protocol for this study was registered in PROSPERO CRD42022352194.